A Novel Promazine Derivative Shows High in vitro and in vivo Antimicrobial Activity Against Staphylococcus aureus - Ronco, Troels; Jørgensen, Nadia S.; Holmer, Iben; Kromann, Sofie; Sheikhsamani, Ehsan; Permin, Anders; Svenningsen, Søren W.; Christensen, Jørn B.; Olsen, Rikke H. (Frontiers in Microbiology, 2020)
The emergence of multidrug-resistant bacteria constitutes a significant public health issue worldwide. Consequently, there is an urgent clinical need for novel treatment solutions. It has been shown in vitro that phenothiazines can act as adjuvants to antibiotics whereby the minimum inhibitory concentration (MIC) of the antibiotic is decreased. However, phenothiazines do not perform well in vivo, most likely because they can permeate the blood-brain (BBB) barrier and cause severe side-effects to the central nervous system. Therefore, the aim of this study was to synthesize a promazine derivate that would not cross the BBB but retain its properties as antimicrobial helper compound. Surprisingly, in vitro studies showed that the novel compound, JBC 1847 exhibited highly increased antimicrobial activity against eight Gram-positive pathogens (MIC, 0.5–2 mg/L), whereas a disc diffusion assay indicated that the properties as an adjuvant were lost. JBC 1847 showed significant (P < 0.0001) activity against a Staphylococcus aureus strain compared with the vehicle, in an in vivo wound infection model. However, both in vitro and in silico analyses showed that JBC 1847 possesses strong affinity for human plasma proteins and an Ames test showed that generally, it is a non-mutagenic compound. Finally, in silico predictions suggested that the compound was not prone to pass the BBB and had a suitable permeability to the skin. In conclusion, JBC 1847 is therefore suggested to hold potential as a novel topical agent for the clinical treatment of S. aureus skin and soft tissue infections, but pharmacokinetics and pharmacodynamics need to be further investigated.